PENGARUH DOSIS PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TERUNG (Solanum melongena L.) - Yustina Maria Silvia Wonga Puu; Elias Nong Sina (Agriculture Faculty of Flores University, 2012)
This research aimed to know the effect and optimum rates of liquid organic fertilizer on the growth and yield of Eggplant. The research used Randomized Block Designconsisted of 5 rates of liquid organic fertilizer;(M0 = control/without fertilizers, M1 = 1 liters ha-1, M2 = 1 ha-2 litres, M3 = 3 liters ha-1, M4 = 4 liters ha-1). The observed variable is the height of plants, number and leaf area, length of fruit, fruit diameter, number of fruit, the weight of fruit per plant, weight of fruit per hectare, fresh residues per plant, and fresh residues per hectare and harvest index. The result of experiment showed the rates of liquid organic fertilizer effect on percentage of the growth and yield of eggplant; they are; height of plants(6,22%), leaf number (28,20%), leaf area (29,58%), length of eggplant (43,11%), eggplant diameter (9,00%), number of eggplant (22,03%), weight of eggplant per plant (25,62%), weight of eggplant per hectare (16,70%), fresh residues per plant (28,58%), residues per hectare (34,93%), and harvest index (53,91%). Optimum rates of liquid organic fertilizer which effect on the growth and yield of eggplant are about 4 litre ha-1.